Environmental factors affecting elite young athletes - Williams, C. (The Elite young athlete, 2011)
To date, much of the research concerning the performance of elite young athletes has focused on physical and physiological factors and how these relate to age and maturation. Little attention has been paid to other factors which might limit performance such as nutrition or environmental stressors. The paucity of research on the environmental effects on performance in young athletes is unsurprising given the need for experimental studies, the ethics of which would generally be untenable. As an outcome, there is a reliance on observational and case study data, e.g. observing the stressors which occur during jet lag and effects on sleep patterns, altitude and pollution. The effects of environmental factors have been predominantly researched from a health context in youngsters rather than a performance context. However, the evidence of those few empirical studies combined with coach and/or sports science support teams` experience have provided professionals with some guidelines. These applied guidelines include sleep patterns, jet lag, pollution and altitude research, to aid those preparing young athletes for training and competition in environments that present potential challenges to performance. The limitations of data extrapolated from adults are acknowledged and in all cases it is emphasised that recommendations and implementing practice should be based on data collected from young people.